Content Creator Strategies on Instagram Reels Account @Kumparancom to Boost Brand Engagement - Maharani, Intan Ayu; Ardhanariswar, Kartika Ayu (Program Studi Ilmu Komunikasi, 2024)
The aim of this study is to uncover the content creator strategies on the Instagram reels of the account @kumparancom in enhancing brand engagement within the #BerkahBersama campaign. This research employs the Goals-Plan-Action theory and the concept of The Circular Model of SOME by Regina Luttrell. This research uses case studies. Data collection involved observation, interviews, and documentation. The research findings indicate that Kumparan's content creators comprehensively follow the phases of the SOME model, namely share, optimize, manage, and engage. Each aspect is executed innovatively, incorporating the creators' creativity and considering the audience's needs. Leveraging the creators' presence, Kumparan is able to establish close interactions and connections with its audience. Not only has it succeeded in achieving engagement with measures like intention to recommend and loyalty, but the #BerkahBersama campaign has also evolved into an inspirational and meaningful social movement. Creators excel at presenting content through creative approaches, including humor, satire, and even sarcasm. Through these strategies, Kumparan successfully heightens brand engagement with its audience. Kumparan is seen as a competent, informative, current, unique, and audience-sensitive media portal.